KESIAPAN MADRASAH DALAM PEMENUHAN STANDAR LAYANAN MINIMAL PENDIDIKAN - Umul Hidayati (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2009)
The results of this research indicate that Islamic schools' preparedness in attaining the minimum education service standards (educators and education personnel according to Education National Standards) is categorked as fair. However, the Islamic schools' preparedness has not either reached ideal condition or maximum level as there are still weaknesses found in several components in terms of educators I teachers, Islamic school principals or supervisors. Teacher competence (at Islamic Elementary School and Islamic Junior High School) is categolked as fair with an average score of 3.9; school principal competence (at Islamic Elementary School and Islamic Junior High School) is categorized as fair with an average score of 3.8; meanwhile, supervisor competence is categoned as fair with an average score of 3.6.